Perifiton heterotrófico : colonização e influência do pulso hidrossedimentológico em uma planície de inundação neotropical. - Fulone, Leandro Junio (2012)
The study aimed to investigate the influence of the flood pulse (limnophase and potamophase), as well as daily fluctuations in water levels on the composition and density of the fraction of heterotrophic periphytic community (rotifers, microcrustaceans and testate amoebae) during the colonization process in an environment of the floodplain of the Paraná River. Accordingly, we tested the following hypotheses: (i) the composition of the fraction of heterotrophic periphytic community differs between limnofases potamofases and (ii) the density of organisms is positively correlated with the values of water levels. For this, an experiment was conducted during two flood pulses between 2009 and 2011: limnophase (L1) (September-October 2009), potamophase (P1) (February-April 2010), limnophase (L2) (August-September 2010 ) and potamophases (P2) (February-April 2011). At each phase of the cycle, artificial substrates were installed in the littoral zone of a environment connected to the Paraná River. The colonization process was followed for 40 days and sampled on the 1st, 4th, 7th, 10th, 14th, 18th, 22nd, 26th, 30th, 34th and 40th days of colonization, totaling 11 samples in each period. The results showed that the fraction of heterotrophic periphytic community reached high densities and diversity in the 10 th day of colonization. Furthermore, it emphasizes the irregularity of the succession, which had several retreats, probably caused by disturbances related to large fluctuations in water levels. Factors such as the presence of sources of dispersion and irregularity of flood pulse were responsible for significant differences in the composition and density of the communities analyzed in each period. Furthermore, the increased density of organisms positive with increasing water levels. Studies are recommended to investigate how the daily fluctuations of water levels can influence periphyton in environments connected to the Paraná river, even when these oscillations are not intense, as well as studies in environments not subject to disturbance, to a better understanding of the succession process heterotrophic periphyton.